When translational neuroscience fails in the clinic: Dexamethasone prior to virtual reality exposure therapy increases drop-out rates. (January 2019) - Maples-Keller, Jessica L.; Jovanovic, Tanja; Dunlop, Boadie W.; Rauch, Sheila; Yasinski, Carly; Michopoulos, Vasiliki; Coghlan, Callan; Norrholm, Seth; Rizzo, Albert Skip; Ressler, Kerry; Rothbaum, Barbara O.
Highlights: Dexamethasone has been shown to facilitate fear extinction in human and animal models. We tested if dexamethasone would improve virtual reality exposure therapy outcomes. Dexamethasone was associated with increased drop-out compared to placebo. Abstract: Posttraumatic stress disorder (PTSD) is characterized by exaggerated expression of fear responses to danger and safety cues. Translational research suggests that dexamethasone facilitates fear extinction in animal and human fear conditioning models. For this randomized, placebo-controlled trial (N = 27), we aimed to translate these findings to the clinic by using virtual reality exposure (VRE) therapy for OEF/OIF/OND veterans with PTSD to determine whether dexamethasone will increase the efficacy of exposure therapy for VRE relative to placebo. VRE sessions involved imaginal exposure to the most traumatic war memories while viewing a computer-generated view of virtual Iraq or Afghanistan with multisensory stimulus options used to match patient's description of the trauma. VRE was effective in reducing PTSD symptoms but there was no interaction with dexamethasone. Drop-out rate was significantly higher in the dexamethasone group, with 10 of 13 (76.9%) participants in this group discontinuing, compared to only 4 of 14 (28.5%) in the placebo group, χ 2  = 6.31, p = 0.02. Results indicate that the dexamethasone group may have experienced an increase in PTSD symptoms, particularly re-experiencing, at session 2 following first drug administration. Contrary to study hypotheses, dexamethasone did not enhance exposure therapy outcomes and was associated with increased drop-out. This demonstrates potential pitfalls in translating neuroscience models to the clinic; future research carefully examining glucocorticoid mechanisms involved in therapy augmentation is warranted.